Covalent functionalization of two-dimensional group 14 graphane analogues. (8th June 2018) - Huey, Warren L. B.; Goldberger, Joshua E.
Abstract : The sp 3 -hybridized group 14 graphane analogues are a unique family of 2D materials in which every atom requires a terminal ligand for stability. Abstract : The sp 3 -hybridized group 14 graphane analogues are a unique family of 2D materials in which every atom requires a terminal ligand for stability. Consequently, the optical, electronic, and thermal properties of these materials can be manipulated via covalent chemistry. Herein, we review the methodologies for preparing these materials, and compare their functionalization densities to Si/Ge(111) surfaces and other covalently terminated 2D materials. We discuss how the electronic structure, optical properties, and thermal stability of the 2D framework can be broadly tuned with the ligand identity and framework element. We highlight their recent application in electronics, optoelectronics, photocatalysis, and batteries. Overall, these materials are an intriguing regime in materials design in which both surface functionalization and solid-state chemistry can be uniquely exploited to systematically design properties and phenomena.